Influence of inflammation on the expression of microRNA-140 in extracellular vesicles from 2D and 3D culture models of synovial-membrane-derived stem cells - Pfeifer, João Pedro Hübbe [UNESP] (2024)
Background: In osteoarthritis (OA), articular homeostasis is regulated by microRNA-140 that inhibits ADAMTS-5, an enzyme that cleaves aggrecan and stimulates the synthesis of other inflammatory mediators. This study aims to evaluate the expression of microRNA-140 in extracellular vesicles (EVs) derived from equine synovial-membrane-derived mesenchymal stem cells (eqSMMSCs) cultured in monolayer (2D) and three-dimensional (3D) culture models under an in vitro inflammatory environment. Methods: Four experimental groups of eqSMMSC cultures were defined for isolation of the EVs. The 2D and 3D control groups were cultured in a conventional cell culture medium, while the 2D-OA and 3D-OA treatment groups were exposed to an OA-like medium containing IL-1β and TNFα. The culture media samples were collected at 24 h, 72 h, and 120 h time points for EV isolation and characterization using nanoparticle tracking analysis (NTA) and transmission electron microscopy (TEM). Reverse transcription quantitative polymerase chain reaction was employed to assess the expressions of microRNA-140 in both the cells and EVs. All statistical analyses were conducted at the 5% significance level. Results: Encapsulation of the eqSMMSCs protected the cells from the inflammatory media compared to the monolayer cultures. EVs were found in higher concentrations in the 3D-OA cultures. Additionally, higher expressions of microRNA-140 were observed in the cells of the 3D-OA group at 24 and 72 h, whereas microRNA-140 expressions in the EVs were higher in the 3D group at 72 h and in the 2D-OA group at 120 h (p < 0.001). However, the 3D-OA culture showed higher expression of the mRNA Adamts5 in the EVs at 120 h. Conclusion: The responses of the eqSMMSCs to inflammatory stimuli involve intracellular expression of microRNA-140 and its subsequent transportation via the EVs, with quicker responses observed in the 3D than 2D cultures. This study sheds light on the behaviors of stem cells in restoring homeostasis in osteoarthritic joints.